Neoadjuvant systemic therapy for hepatocellular carcinoma - Chick, R. Connor; Ruff, Samantha M.; Pawlik, Timothy M. (Frontiers in Immunology, 2024)
Surgical resection and liver transplant remain the only curative therapies for most patients with hepatocellular carcinoma (HCC). Systemic therapy options have typically been ineffective, but recent advances, such as the combination of immune checkpoint inhibitors and targeted therapies, have shown great promise. Neoadjuvant systemic therapy in resectable or locally advanced HCC is under active investigation with encouraging results in small, early-phase trials.Many of these completed and ongoing trials include combinations of systemic therapy (e.g. immune checkpoint inhibitors, tyrosine kinase inhibitors), transarterial therapies, and radiation.Despite early successes, larger trials with evaluation of long-term oncologic outcomes are needed to determine the role of neoadjuvant systemic therapy in patients with HCC who may be eligible for curative intent surgery or transplant.